A study on the determinants of leisure travel spending. - Ling, Wai Ming. (2008)
This research examines the relationship between travel expenditure and the variables; real income, consumer confidence, financial well-being and the perceived price of travel. The 120 responses collected were analysed using multiple regression and Pearson's correlational tests. Results indicated that real income and consumer confidence were both strong explanatory variables for leisure travel spending, while financial well-being was not. Travel fair attendance and housing types were also found to correlate with travel spending.